The sociology of religion in India: past, present and future - Sardella, Ferdinando (Abhijeet Publications, 2013)
Papers presented at the conference on "The Interface between East and West, Multiculturalism and Identity: What Can Sociology and Religious Studies Contribute to the Making of a Better Society" organized by Department of Sociology, Jadavpur University during 10-12 June 2009